2013
DOI: 10.4172/2161-069x.s2-004
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Intra-Gastric Resection of Gastric Sub-Mucosal Tumors under Oral Endoscopic Guidance

Abstract: Introduction: A laparoscopic approach is often selected for resection of gastric submucosal tumor (GST), and several variations of this procedure have been reported. The approach selected greatly depends on the characteristics of the tumor, including its size or location, and also the experience and skill of the surgeon. Here we report our experience with intragastric resection of GSTs under oral endoscopic guidance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A combined laparoscopic–endoscopic approach has been utilized in a number of patients with tumours close to the OGJ [ 1 , 2 , 9 ], but there is a paucity of literature in this area (particularly in the UK) on details such as success rates, complications and follow-up. Taniguchi et al [ 10 ] reported a case study of a patient undergoing successful LECS of a tumour located in the cardia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A combined laparoscopic–endoscopic approach has been utilized in a number of patients with tumours close to the OGJ [ 1 , 2 , 9 ], but there is a paucity of literature in this area (particularly in the UK) on details such as success rates, complications and follow-up. Taniguchi et al [ 10 ] reported a case study of a patient undergoing successful LECS of a tumour located in the cardia.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature suggests a number of advantages to this technique. Decreased deformity or stenosis of the OGJ, precise tumour location, determination of stomach port sites, confirming haemostasis at the staple line, retrieval of tumour and checking for air leakage post-resection have all been suggested as likely advantages of LECS [ 2 , 9 ]. Furthermore, endo-linear stapler usage minimizes potential blood loss during tumour resection, decreases operation time and requires no suturing of resected stomach wall.…”
Section: Discussionmentioning
confidence: 99%